Efektivitas Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas 2 SD - Erni, Yuli (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to determine the effectiveness of the Problem Based Learning model to improve mathematics learning outcomes for second grade students at SDN 31 VII Koto Sungai Sarik. This research is Classroom Action Research (CAR). The learning outcomes of cognitive aspects in the first cycle have increased from the initial ability test with an average value of 60.23% to 86.74%. The affective aspect of learning outcomes obtained an average score of 21.07% in the sufficient category and the psychomotor aspect learning outcomes obtained an average score of 24.57% in the sufficient category. So there is an increase in learning outcomes from the initial ability test to the first cycle, which is 26.51%. In cycle II, learning outcomes have increased again, namely in the cognitive aspect with an average value of 86.74%; affective aspect with an average score of 28.43% in good category; and psychomotor aspect learning outcomes with an average score of 32.62% in the good category. These results indicate that the Problem Based Learning model can improve student learning outcomes in Mathematics class 2 SDN 31 VII Koto Sungai Sarik.